Análisis de la relación entre el tipo de turismo y el nivel de ingreso económico de los turistas que visitan la provincia de Pichincha. - Túquerres Suntaxi, Grace Alexandra (2023)
The research was carried out in the province of Pichincha, its objective was to analyze the relationship between the type of tourism and the level of economic income, the research was cross-sectional. For the development of the project, documents such as: (PD y OT), surveys carried out by the academy, Ministry of Tourism, Quito Tourism, theses, brochures, official pages of Pichincha that allowed identifying the types of tourism that are practiced, were reviewed. For the selection of tourist attractions, the Methodology Manual for the Hierarchy of Attractions and Generation of Tourist Spaces was used, in addition, a document called Atractivos Pichincha cut May 2023 was obtained, which was provided by the Ministry of Tourism, which was used as a guide for the selection of tourist attractions. In the second objective, the survey was used as a technique and the questionnaire as an instrument, which was prepared jointly with the research teacher, consisted of two variables: demographic and socioeconomic, to carry out the calculation of the sample, the study population was defined. Not finding exact data, the infinite population formula was applied (Fernández-Morales, 2002), with a relative standard error of 5%, confidence level of 95%. A database was prepared for this, the statistical method was used, as an Excel tool and finally for the third objective the correlation between the two study variables was defined. As a result of the investigation, it was obtained that the types of tourism carried out by tourists in the province of Pichincha are: cultural, gastronomic and natural. The selected attractions were: Virgen el Panecillo Monument, "Fray Pedro Gocial" Museum - San Francisco Church, Machachi Mother Church, San Juan Bautista de Sangolquí Church, Eduardo Kigman House Museum, belonging to cultural tourism in hierarchy III, the Condor Waterfall Machay, “Las Gemelas” Waterfall, “Corazón de Piedra” Waterfall, Cueva Iris Natural Tourism Cave and as gastronomic tourism, Hornado de Sangolquí, are located in hierarchy II. As a result of the 385 surveys, it was obtained that 62% are older adults since they are in the age range of 25 to 59 years, 51% are women, of Ecuadorian nationality who reside in Quito and in the Rumiñahui canton, the 48% are married, 45% have a higher education level, 65% have a job, 27% belong to the private sector, 32% have an income of $801 to $1,500. In the statistical test, a significant result was obtained at the bilateral level 0.01, which shows a relationship between the two study variables: type of tourism and level of economic income of the tourist who visits Pichincha.